Transcriptomic Analyses of Myeloid-Derived Suppressor Cell Subsets in the Circulation of Colorectal Cancer Patients - Sasidharan Nair, Varun; Saleh, Reem; Toor, Salman M.; Alajez, Nehad M.; Elkord, Eyad (Frontiers in Oncology, 2020)
Myeloid-derived suppressor cells (MDSCs) promote tumor immune evasion and favor tumorigenesis by activating various tumor-promoting downstream signals. MDSC expansion is evident in the circulation and tumor microenvironment of many solid tumors including colorectal cancer (CRC). We have recently reported the transcriptomic profiles of tumor-infiltrating MDSCs in CRC patients and uncovered pathways, which could potentially assist tumor progression. In this study, we sorted different subsets of circulating MDSCs in CRC patients and investigated their transcriptomic profiles in order to disclose pathways, which could potentially contribute to disease progression. The sorted subsets included polymorphonuclear/granulocytic MDSCs (PMN-MDSCs), immature MDSCs (I-MDSCs), and monocytic MDSCs (M-MDSCs). Our functional annotation analyses revealed that multiple pathways including DNA damage-, chemotaxis-, apoptosis-, mitogen-activated protein kinase-, transforming growth factor β-, and myeloid differentiation–related transcripts were higher in PMN-MDSCs, compared with monocytic antigen-presenting cells (APCs) or I-MDSCs. Furthermore, genes related to Janus kinase (JAK)–signal transducer and activator of transcription (STAT) were also elevated in PMN-MDSCs. These data suggest that upregulation of JAK-STAT pathway could trigger multiple downstream targets in PMN-MDSCs, which favor tumor progression. Additionally, we found that pathways including phosphatidyl inositol 3-kinase (PI3K), interleukin 6, and TGF-β in M-MDSCs and cell cycle–related pathways in I-MDSCs were upregulated, compared with monocytic APCs. Moreover, acetylation-related genes were upregulated in both PMN-MDSCs and M-MDSCs. This latter finding implicates that epigenetic modifications could also play a role in the regulation of multiple tumor-promoting genes in PMN-MDSCs and M-MDSCs. Taken together, this study reveals various signaling pathways, which regulate the function of MDSC subsets in the circulation of CRC patients. However, functional studies are warranted to support these findings.